Analisis bauran pemasaran 5P yang diterapkan CV. Kajeye Food dalam meningkatkan penjualan - Tushofiyah, Sa’ida (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze the 5P marketing mix applied by CV Kajeye Food to increasing sales. In this study, researchers collected data by interviewing the owner of CV Kajeye Food and collecting files related to the company. The results showed that CV Kajeye Food uses the 5P marketing mix strategy in increase sales of its products. By promoting the quality of its products, choosing a strategic place, providing affordable prices by calculating the appropriate price, promoting products by utilizing digital, and recruiting employees who are capable in their fields and targeting tourists as buyers of their products.